Marriage, Cohabitation and Participation in Domestic Labor: Men and Women in Contemporary Italy - Arosio, Laura (European Scientific Journal, ESJ, 2017)
This work aims to study whether cohabiting couples tend to introduce new patterns in the allocation of domestic labor compared to married couples or if emergent family arrangements tend to follow traditional models. After a discussion of the theoretical issues involved, the results of an analysis on the time spent by partners on domestic labor will be presented. This analysis focuses on differences in the type of relationship individuals are in; that is, whether they are married or cohabiting. A comparison between men and women will be carried out. The data used in the analyses come from the national representative survey “Multi-Purpose Family Survey – Aspects of Daily Life”, carried out in 2012 by the Italian National Institute of Statistics (ISTAT). The results suggest that even after taking into account other factors which tend to affect time spent in domestic labor, cohabitation appears to be a different model of partnership for women as opposed to marriage. This result is not valid for men. Men and women show different patterns of involvement into domestic labor and family life.